Health service utilisation cost associated with residential fire incidents in New South Wales, Australia - Fahmida Saadia Rahman; Wadad Kathy Tannous; Kingsley Emwinyore Agho; Gulay Avsar; Lara Ann Harvey (BMC Health Services Research)
Abstract Background Fire is a major contributor to global fatalities and disabilities and remains a prevalent threat to individuals in Australia. New South Wales (NSW) experiences over one-third of all structure fires, including residential ones, in the country and one-quarter of all associated deaths and hospital admissions. In an atmosphere of rising healthcare cost and heightened demand for its services, obtaining total cost data for residential fires is essential. The study aims to estimate the cost of health service utilisation, including ambulance, emergency, and hospital admission, resulting from residential fire incidents in NSW, Australia. Method This population-based cohort study uses response and health service administration data from 1 January 2005 to 31 December 2014. The data sources are Australian Computer Aided Dispatch system, Fire and Rescue NSW Australian Incident Reporting System, NSW Ambulance datasets, NSW Emergency Department Data Collections, and NSW Admitted Patient Data Collection which are administrative datasets that have been linked. Cost figures were expressed in constant 2023 Australian dollars. Results The estimated annual average cost for ambulance use was AU$75 thousand, with the average cost per use of AU$945. The average annual cost for emergency department visits was AU$137 thousand, and the average cost per visit was AU$890. The average total length of stay in hospital was nine days. The average annual cost of episodes of care in hospital was estimated at AU$4 million, with the average cost per episode of care of AU$16,140. The study assessed the total cost for health service use relevant to residential fire incidents and associated injuries at AU$46 million over time, averaging approximately AU$5 million annually. Conclusion This study provided, for the first time, total and average costs of health service utilisation per type for ambulance use, ED visits, and hospital admissions associated with residential fire incidents and related injuries using linked administrative data in NSW. Our study will assist the government and stakeholders in making informed decisions that prioritise funding for healthcare service and improve the quality of overall fire safety and public health outcomes.